2021
DOI: 10.24815/jks.v21i2.20376
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Ekstrak Ikan Gabus Terhadap Kesembuhan Luka Diabetes

Abstract: Abstrak. Luka diabetes merupakan luka kronis yang berdampak buruk bagi morbiditas, mortalitas, dan psiko-sosio-ekonomi penderita maupun keluarganya. Kondisi hiperglikemia mengakibatkan fase penyembuhan luka tidak berjalan normal. Ekstrak ikan gabus, yang dapat diberikan peroral maupun sebagai bahan kombinasi penutup luka berpotensi terhadap penyembuhan luka diabetes melalui peningkatan jumlah netrofil dan makrofag, neovaskularisasi. Selain itu, ekstrak ikan gabus meningkatkan jumlah fibroblas, deposisi kolagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The results of rigorous statistical analysis confirmed that the albumin activity of chitosan nanoparticles derived from extracted snakehead fish, which has its origins in the natural habitat of Kalimantan, produced a significant positive impact in accelerating the wound healing process after tooth extraction when compared with the control group that did not receive similar treatment. This indicates the potential use of extracted snakehead fish in the context of wound healing therapy and highlights its effectiveness in improving the tissue healing process after tooth extraction in white rats (Prayugo et al, 2021;Utami et al, 2020).…”
Section: Experimen Tal Laboratorymentioning
confidence: 82%
“…The results of rigorous statistical analysis confirmed that the albumin activity of chitosan nanoparticles derived from extracted snakehead fish, which has its origins in the natural habitat of Kalimantan, produced a significant positive impact in accelerating the wound healing process after tooth extraction when compared with the control group that did not receive similar treatment. This indicates the potential use of extracted snakehead fish in the context of wound healing therapy and highlights its effectiveness in improving the tissue healing process after tooth extraction in white rats (Prayugo et al, 2021;Utami et al, 2020).…”
Section: Experimen Tal Laboratorymentioning
confidence: 82%
“…When the antioxidants produced by the human body are not enough to fight free radicals, the body requires antioxidant intake from outside. Consumption of foods that contain antioxidant agents can help the body to reduce the content of free radicals in the body [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The role of albumin is also as a basic ingredient for collagen formation. Collagen is one type of protein that reaches 30% of all proteins that make up the human body [1,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Snakehead fish protein contains main nutrients consisting of protein and fat of 78% and 2%, respectively (Prayugo et al, 2021). Snakehead fish protein content can reach 25.5% (Alfarisy, 2014).…”
Section: Protein Qualitative Testmentioning
confidence: 99%
“…Wound healing is a natural phenomenon of the body's repair process in overcoming tissue damage to the skin (Prayugo et al, 2021). The natural rate of wound healing is very slow and the chance of being infected with microbes is very high.…”
Section: Introductionmentioning
confidence: 99%